2016
DOI: 10.1155/2016/7618342
|View full text |Cite
|
Sign up to set email alerts
|

miR-940 Suppresses Tumor Cell Invasion and Migration via Regulation of CXCR2 in Hepatocellular Carcinoma

Abstract: Aim. To investigate the expression of miR-940 in the hepatocellular carcinoma (HCC) and its impact on function and biological mechanism in the HCC cells. Methods. Quantitative RT-PCR analysis was used to quantify miR-940 expression in 46 cases of tissues and cells. Transfection of HCC cell lines was performed by miR-940 mimics; the abilities of invasion and migration were assessed through Transwell array. Western blot represents the alteration in expression of CXCR2 by miR-940 mimics. Results. miR-940 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 24 publications
(20 reference statements)
4
41
0
Order By: Relevance
“…Rajendiran et al have reported that miR-940 is downregulated significantly in prostate cancer and suppresses cell migration and invasion [38]. In HCC, miR-940 was also found to be significantly decreased in the HCC tissues and cell lines, and function as a tumor suppressor through inhibition of invasion and migration of HCC cells [39,40]. Consistently, our present study showed that miR-940 was involved in the overexpression of H1HR in HCC cells.…”
Section: Discussionsupporting
confidence: 89%
“…Rajendiran et al have reported that miR-940 is downregulated significantly in prostate cancer and suppresses cell migration and invasion [38]. In HCC, miR-940 was also found to be significantly decreased in the HCC tissues and cell lines, and function as a tumor suppressor through inhibition of invasion and migration of HCC cells [39,40]. Consistently, our present study showed that miR-940 was involved in the overexpression of H1HR in HCC cells.…”
Section: Discussionsupporting
confidence: 89%
“…It was reported in many studies that miR-940 was highly expressed in normal tissues compared with tumors, and miR-940 was shown to inhibit the migratory and invasive potential of cancer cells by suppressing CXCR2 [59], MIEN1 [58], MyD88 [57], Nestin [56], and ZNF24 [54]. Moreover, the Estrogen-Related Receptor Gamma (ESRRG) was targeted by miR-940, and suppression of ESRRG inhibited hepatocellular carcinoma cell lines growth and induced cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…miR-940 was previously demonstrated to be aberrantly expressed in a number of types of human cancer. miR-940 was downregulated in hepatocellular carcinoma, and this downregulation was significantly associated with Edmondson grade, tumor microsatellite or multiple tumors, vascular invasion, recurrence and metastasis (18,24). Patients with hepatocellular carcinoma and low miR-940 expression levels exhibited poorer prognosis compared with high expression levels (18).…”
Section: Discussionmentioning
confidence: 98%
“…MicroRNAs (miRNAs) comprise a series of endogenous, short single-stranded non-coding RNAs (19)(20)(21)(22)(23)(24)(25) molecules) that primarily serve as gene regulators (8). These molecules negatively regulate gene expression by directly binding to partial complimentary sites in the 3'-untranslated regions (3'-UTRs) of their target genes, resulting in mRNA degradation or inhibition of translation (9).…”
Section: Introductionmentioning
confidence: 99%